أســـاس وطبيعـــة الإعتـــراف الـــدولــــي (مجلة الواحات للبحوث والدراسات, 2017)
Recognition In Contemporary International Public Law Is A Political Legal Act, Translated By The Intentions Of A Member Country Of The International Community, Towards An Emerging State That Wishes To Join The International System. Recognition May Be An Expression In An Organized Form And Is Based On New Facts, Which Are Made Up Of A Government Within A State, Capable Of Maintaining Peace And Fulfilling Commitments. In Order To Recognize A Multidimensional Nature, Its Effects Are Realistically Felt In Unilateral Actions By Countries That Are Traditionally Contemplated, Far From Respecting International Laws, Customs, Conventions And Norms, And Do Not Take Into Account The Principle Of State Sovereignty And The Free Choice Of People. Key Words - Recognition  -  International Public Law - Emerging State– Legtimascy Government.